First Clinical Results of Modular Intraocular Lens Implantation - E. N. Batkov; T. F. Artemyeva; N. P. Pashtayev; N. A. Pozdeyeva (Oftalʹmologiâ, 2021)
Introduction. Recent population studies reveal steady growth in intraocular lens (IOL) exchanges including those for refractive and other optical reasons. To lower complication risks related to IOL exchange, we introduced a modular IOL model with replaceable optical part.Purpose: preliminary analysis of modular IOL implantation clinical results.Patients and methods. From August 2018 to February 2020, five patients as part of their surgical treatment for various forms of cataract received newly designed modular IOLs. The modular IOL is composed of two separate parts — haptic and optic, manufactured from the same elastic acrylic material with hydrophobic properties. The haptic includes a closed ring and a pair of open equally distant loops in a unified design. The haptic ring with projections serves as a base for optical disk. The current study evaluated characteristics of the IOL implantation and assembly process, as well as possible development of intra- and early postoperative complications.Results. First implantations of the modular IOL accomplished using standard surgical instrumentation and disposables passed without complications. We did not observe scratches, breaks or any other mechanical damage to neither haptic, nor optical parts. During simultaneous implantation, optical disks fixated in haptic rings preserved their due positioning after transiting through slender injector channel. There were no specific, modular-IOL related complications in the early postoperative period. The optical disk maintained correct location, delimited by fixation leaflets of the haptic ring.Conclusion. Early results for clinical application of the novel modular IOL demonstrated feasibility of its safe implantation in disassembled and preassembled modes.